Digital Empowerment and Financial Literacy for Rural Youth: Unlocking Inclusive Growth in Indonesia - Budiman, Arief (KRIEZ ACADEMY : Journal of development and community service, 2024)
This paper examines the critical role of digital competencies and financial literacy among rural youth in Indonesia as a foundational pillar for achieving inclusive economic growth. Despite a rapidly expanding digital economy, rural youth often remain at the periphery, facing significant barriers to effective participation in formal financial systems due to limited access to infrastructure, a lack of targeted knowledge, and a scarcity of appropriate digital tools. Employing a qualitative-dominant mixed-methods research design, this study combines survey data from 220 youth in rural areas of West Java and Central Java with insights from focus group discussions (FGDs) and in-depth case studies of three community-based financial literacy initiatives. The research highlights a clear and compelling connection: when access to digital tools and mobile finance platforms is combined with contextualized and practical financial education, it significantly impacts entrepreneurial aspirations, savings behavior, and overall participation in the formal economy. The findings reveal that increased digital fluency, alongside a stronger grasp of financial concepts, fosters the creation of microenterprises, promotes responsible savings habits, and facilitates upward economic mobility in underserved regions. This paper concludes that unlocking the immense potential of rural youth requires a holistic and collaborative approach from government, fintech actors, and educational institutions to implement scalable, culturally adapted, and technology-enabled financial literacy models.